The Effect Of Lifestyle, Price And Promotion On Purchase Decision Of Consumers Kasta Coffee Batam - Adhila, Bella Tasya Adhila; Raymond, Raymond (Zona Manajerial: Program Studi Manajemen (S1), 2021)
This study aims to determine the influence of Lifestyle, Price and Promotion on the Purchasing Decisions of Consumers Kasta Coffee Batam. The method used is a quantitative method. The population in this study was Consumers of Kasta Coffee with a total of 9,245 consumers. The sample used was 100 respondents. The data collection technique used in this study was through an online questionnaire. The data analysis technique in this study used Multiple Linear Regression using SPSS software version 25. The results of this study show that lifestyle has a positive significant effect on the purchasing decisions of consumers of Kasta Coffee Batam with a probability value of 0.000 < 0.05. Price has a positive significant effect on the purchasing decisions of consumers of Kasta Coffee Batam with a probability value of 0.000 < 0.05. Promotion has a positive insignificant effect on the purchasing decisions of consumers of Kasta Coffee Batam with a probability value of 0.757 > 0.05. The value of the Coefficient of Determination of 70.6% shows the contribution of Lifestyle, Price and Promotion to the Purchasing Decision of Consumers Kasta Coffee Batam and the remaining 29.4% is explained by other variables.